2011
DOI: 10.1161/atvbaha.111.232348
|View full text |Cite
|
Sign up to set email alerts
|

Age as a Modulator of Inflammatory Cardiovascular Risk Factors

Abstract: Objective Levels of acute phase reactants are impacted by age. To what extent cardiovascular risk associated with aging is due to an increase in the inflammatory burden is not known. We assessed the relationship with age of inflammatory markers, representing a) systemic (C-reactive protein [CRP], fibrinogen and serum amyloid-A [SAA]) and b) vascular (lipoprotein-associated phospholipase A2 [Lp-PLA2] and pentraxin-3 [PTX-3]) inflammation. Methods and Results We determined Lp-PLA2 mass and activity, CRP, fibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 37 publications
2
26
0
1
Order By: Relevance
“…To collectively assess the trend patterns of the relationship between age and inflammatory markers, we constructed a composite z-score for each marker category (systemic or vascular inflammation) based on respective five and three different markers. This approach allows a comparison of individual inflammatory markers within each category at the same scale and provides a standardized way to assess the relative contribution of individual markers to the association with age 19 . Coefficient estimates for mixed-effects regression models associating age, ethnicity/race, and age-race interaction with the composite z-scores of systemic and vascular inflammation with and without adjustments for covariates are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To collectively assess the trend patterns of the relationship between age and inflammatory markers, we constructed a composite z-score for each marker category (systemic or vascular inflammation) based on respective five and three different markers. This approach allows a comparison of individual inflammatory markers within each category at the same scale and provides a standardized way to assess the relative contribution of individual markers to the association with age 19 . Coefficient estimates for mixed-effects regression models associating age, ethnicity/race, and age-race interaction with the composite z-scores of systemic and vascular inflammation with and without adjustments for covariates are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…PTX-3 concentration was assessed by ELISA using a commercially available kit (Enzo Life Sciences. Inc., Plymouth Meeting, PA) 19, 24 . Analyses were run according to the manufacturers’ specifications in duplicate samples with two different quality controls, which were within the recommended precision for each test.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…16 In our study, although serum LDL cholesterol levels showed no significant differences among body size phenotypes, vascular inflammation, represented as maximum TBR, in the MHO group was significantly greater than that of the MHNW group, even after adjusting for age, which is an important modulator of inflammatory CV risk factor. 17 Furthermore, many previous studies have shown that an increased hsCRP level is associated with an increased risk of CV events even after adjustment for traditional risk factors and hsCRP has been found in atherosclerotic plaques. 18 Vascular inflammation precedes the traditional risk factors.…”
Section: Discussionmentioning
confidence: 99%